Age of identification of sensorineural hearing loss and Characteristics of affected children: Findings from two cross-sectional studies in Saudi Arabia. (July 2019) - Alkahtani, Rania; Rowan, Daniel; Kattan, Nad; Alwan, Nisreen A.
Abstract: Objectives: To identify the average age of identification (AOI) and characteristics of Saudi children with sensorineural hearing loss (SNHL). Methods: Two cross-sectional studies were undertaken. Study A: the medical records of 1166 children aged 0–10 years old who visited the audiology clinics in four hospitals in Riyadh and Dammam during 2015 were reviewed. Study B: 174 carers of children aged 0–12 years who visited the audiology clinics in four hospitals in Riyadh during a three-month period were surveyed. Results: The mean AOI with SNHL in children was 3.2 years (SD = 2.5 years) and 3.1 years (SD = 2.6 years) with 14% and 16% not identified until after primary school age for Studies A and B, respectively. The presence of SNHL was positively associated with parental consanguinity, positive family history of SNHL, history of chemotherapy treatment, brain pathology and prior parental concern regarding their child's hearing. Conclusion: AOI of SNHL among Saudi children is deemed high in relation to the likely age of onset, with about 15 in 100 children identified after school age. Childhood hearing screening programmes (at birth and at school entry) should be considered in order to intervene earlier.